Wireless Sensor Networks for Swift Bird Farms Monitoring - Othman, A.K.; Lee, K.M.; Zen, H.; Wan Zainal Abidin, W.A; Sabri, M.F.M. (IEEE, 2009)
This paper provides an in-depth study of Wireless Sensor Network (WSN) application to monitor and control the swift habitat. A set of system is designed and developed which includes the node's hardware, GUI software, sensor network, and interconnectivity for remote data access and management. System architecture is proposed to address the requirements for habitat monitoring. The application driven designed, provides and identifies important areas of work in data sampling, communications and networking. In this monitoring system, a sensor node (MTS400), IRIS and Micaz radio transceivers, and a USB interfaced gateway base station of Crossbow (Xbow) Technology WSN are employed. The Graphical User Interface (GUI) is written using a Laboratory Virtual Instrumentation Engineering Workbench (LabVIEW) along with Xbow Technology drivers provided by National Instrument. This monitoring system is capable of collecting data and presents it in both tables and waveform charts for further analysis. This system is also able to send notification messages by e-mail, whenever changes on the swift habitat at remote sites (swift farms) occur, via the Internet connectivity. Other functions that have been implemented in this system are the database system for record and management purposes; remote access through the internet using LogMeIn software. Finally, this research draws a conclusion that a wireless sensor network for monitoring swift habitat can be effectively used to monitor and manage swift farming industry in Sarawak.